2007
DOI: 10.1111/j.1745-4557.2007.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

COLD‐CONDITIONING TREATMENT REDUCES CHILLING INJURY IN MEXICAN LIMES (CITRUS AURANTIFOLIA S.) STORED AT DIFFERENT TEMPERATURES

Abstract: Induction of different antioxidant enzymes by high and low temperatures prior to storage has been reported to produce tolerance to chilling injury (CI). Thus, different prestorage temperatures have been suggested to decrease CI in citrus fruits. In this work, the effectiveness of a cold‐conditioning treatment (13C for 48 h) to prevent CI was evaluated in Mexican limes (Citrus aurantifolia S.) stored at 4, 10 and 25C, and 90% relative humidity. Cold conditioning reduced 1.6‐fold CI symptoms, induced a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(88 reference statements)
0
4
0
1
Order By: Relevance
“…The analysis has also shown that high-temperature conditioning might protect citrus fruit against CI by scavenging ROS through enzymes like SOD, glutathione transferase (GST), glutaredoxin, tioredoxin, as well as different metalloproteins (Table S1 ). These results add further knowledge about the enzymes that protect cold-stored citrus fruit from oxidative stress, and demonstrate that such protection in citrus fruits is not limited only to the traditional SOD, catalase, peroxidase, and Halliwell-Asada cycle antioxidant enzymatic system (Sala and Lafuente, 2000 ; Sanchez-Ballesta et al, 2003 ; Rivera et al, 2007 ; Ghasemnezhad et al, 2008 ; Siboza et al, 2014 ; Lado et al, 2016 ). Likewise, the heat-conditioning treatment repressed lipases and hydrolases in cold-stressed fruits and could, therefore, reduce ROS formation associated with membrane damage.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The analysis has also shown that high-temperature conditioning might protect citrus fruit against CI by scavenging ROS through enzymes like SOD, glutathione transferase (GST), glutaredoxin, tioredoxin, as well as different metalloproteins (Table S1 ). These results add further knowledge about the enzymes that protect cold-stored citrus fruit from oxidative stress, and demonstrate that such protection in citrus fruits is not limited only to the traditional SOD, catalase, peroxidase, and Halliwell-Asada cycle antioxidant enzymatic system (Sala and Lafuente, 2000 ; Sanchez-Ballesta et al, 2003 ; Rivera et al, 2007 ; Ghasemnezhad et al, 2008 ; Siboza et al, 2014 ; Lado et al, 2016 ). Likewise, the heat-conditioning treatment repressed lipases and hydrolases in cold-stressed fruits and could, therefore, reduce ROS formation associated with membrane damage.…”
Section: Resultsmentioning
confidence: 69%
“…They encode proteins of different families, including zing finger proteins, MYB, a co-regulator transcriptional SEUSS, and an auxine response factor (ARF), whose expression only increases in non-conditioned fruits. The role of this hormone in the chilling tolerance of citrus fruits is unknown, but auxines may play a protecting role against oxidative stress (Kovtun et al, 2000 ), which has been associated with CI in Fortune mandarin (Sala and Lafuente, 1999 ; Sanchez-Ballesta et al, 2003 ) and other citrus cultivars (Sala et al, 2005 ; Rivera et al, 2007 ; Ghasemnezhad et al, 2008 ; Maul et al, 2008 ; Lado et al, 2016 ). The transcriptomic analysis also showed slight differences in the expression of two TFs from the YABBY and two from the HSTF families, which showed a higher expression in cold-stored fruits if they had not been previously conditioned at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent warming (IW), hot air, vapor heat, and hot water (HW) are all examples of possible HT applications [ 86 ]. HT have been demonstrated to effectively reduce low-temperature storage damage when applied to fresh produce before cold storage [ 87 ]. Several factors may contribute to the mitigation of chilling in heat-treated fruits and vegetables.…”
Section: Factors Affecting Chilling Injury Incidencementioning
confidence: 99%
“…This difference might be explained by the origin of Atlixco variety from warmer regions than those in where Milpa Alta is produced. Also, unlike Milpa Alta nopal, Atlixco did not show darkening in the zones without spines, probably due to a cross-tolerance mechanism by which CI is perceived by the tissue as more harmful than the physical damage from the spines removal (Saltveit, 2000;Rivera et al, 2007). The presence of damage by pitting in a degree higher than 1.0 adversely affected the visual appearance of nopal Atlixco; therefore, it was assumed that the shelf life was over with pitting indexes ≥ 1.0 (more than 5 % of affected surface).…”
Section: Córdoba Et Al 2011mentioning
confidence: 97%